Shallots skin peeler machine - Kamaruddin, Muhammad Hazeem; Yac’cob, Muhammad Afiq Adham; Mohd Haizan, Mohamad Azrul Azhad; Amiruddin, Fatin Nur Ainina; Hassan, Mohd Fahrul; Muhmad Afandi, Farah Danieza (Penerbit UTHM, 2017)
Shallots have been a popular food for many centuries. Today, they are valued for their flavor, aroma and taste, being prepared domestically or forming raw materials for a variety of food processors. They are probably the most universally used vegetables in most countries. Shallots skin peeling is an essential step in producing many of the shallot products.